2005
DOI: 10.1159/000086771
|View full text |Cite
|
Sign up to set email alerts
|

An Early Phase II Study of S-1 in Patients with Metastatic Pancreatic Cancer

Abstract: Objective: The aim of this study was to evaluate the efficacy and toxicity of S-1 in patients with metastatic pancreatic cancer. Methods: Patients were required to have a histological diagnosis of pancreatic adenocarcinoma with measurable metastatic lesions, and no prior chemotherapy. S-1 was administered orally at 40 mg/m2 twice daily for 28 days with a rest period of 14 days as one course. Administration was repeated until the appearance of disease progression or unacceptable toxicity. A pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 35 publications
4
76
0
Order By: Relevance
“…11) We selected S-1, another active drug in Asian countries including Japan, for pancreatic cancer. S-1 showed noninferiority to gemcitabine in Japanese large-scale trials, 12,13) and we also previously reported that S-1 improved the survival time of patients with unresectable pancreatic cancer. 14,15) Mycophenolate mofetile was discontinued because both mycophenolate mofetile and S-1 combination share the characteristics of DNA synthesis inhibition and simultaneous administration of the two drugs may increase the risk of myelosuppression.…”
Section: Discussionsupporting
confidence: 52%
“…11) We selected S-1, another active drug in Asian countries including Japan, for pancreatic cancer. S-1 showed noninferiority to gemcitabine in Japanese large-scale trials, 12,13) and we also previously reported that S-1 improved the survival time of patients with unresectable pancreatic cancer. 14,15) Mycophenolate mofetile was discontinued because both mycophenolate mofetile and S-1 combination share the characteristics of DNA synthesis inhibition and simultaneous administration of the two drugs may increase the risk of myelosuppression.…”
Section: Discussionsupporting
confidence: 52%
“…5-fluorouracil has been used for chemoradiation because it can enhance the effects of radiation (Whittington et al, 1995;Ishii et al, 1997). The novel oral anticancer agent S-1 was developed to improve the tumor-selective toxicity of 5-FU and has shown a good efficacy for a variety of solid tumours, including pancreatic cancer (Koizumi et al, 2000;Ohtsu et al, 2000;Kawahara et al, 2001;Ueno et al, 2005). Thus, S-1 may also act as a radiosensitizer because it has cytotoxic mechanisms similar to those of 5-FU (Hirata et al, 1999;Hoff et al, 2003;Schoffski, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…S-1 has already undergone phase I and phase II testing in several solid tumours in Japan and Western countries (Koizumi et al, 2000;Ohtsu et al, 2000;van Groeningen et al, 2000;Kawahara et al, 2001;Hoff et al, 2003;Ueno et al, 2005;Nakamura et al, 2006). The main adverse reaction was myelosuppression in a Japanese phase-I study, and diarrhoea in a European and a North-American phase-I study (van Groeningen et al, 2000;Hoff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, several phase II studies demonstrated the efficacy of S-1 in major solid cancers. Response rates of S-1 were 45.0% in gastric cancer [6,7], 32.6% in colorectal cancer [8,9], 18.2% in lung cancer [10,11], 41.7% in breast cancer [12], and 32.2% in pancreatic cancer [13,14]. In addition, the response rate of S-1 was 34.1% in head and neck cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%